Prevalence of oesophageal eosinophils and eosinophilic oesophagitis in adults: the population-based Kalixanda study. Issue 5 (29th November 2006) - Ronkainen, Jukka; Talley, Nicholas J; Aro, Pertti; Storskrubb, Tom; Johansson, Sven-Erik; Lind, Tore; Bolling-Sternevald, Elisabeth; Vieth, Michael; Stolte, Manfred; Walker, Marjorie M; Agréus, Lars
Abstract : Background: Eosinophilic oesophagitis may be increasing but the prevalence in the general population remains unknown. Our aim was to assess this and the presence of eosinophils in the distal oesophageal epithelium in the community. Methods: Oesophagogastroduodenoscopy was performed in a random sample (n = 1000) of the adult Swedish population (mean age 54 years, 49% men). Oesophageal biopsy samples were obtained from 2 cm above, and at, the Z-line. Any eosinophil infiltration of the epithelium was defined as "eosinophils present". Definite eosinophilic oesophagitis was defined as ⩾20, probable as 15–19, and possible as 5–14 eosinophils/high-power field (HPF, at magnification ×40) in oesophageal biopsy specimens. Results: Eosinophils were present in 48 subjects (4.8%, 95% CI 3.5 to 6.1%, mean age 54 years, 63% men), in 54% without troublesome reflux symptoms. Definite eosinophilic oesophagitis was present in four subjects (0.4%, 95% CI 0.01 to 0.8%, mean age 51 years, 75% men) and probable eosinophilic oesophagitis in seven subjects (0.7%, 95% CI 0.2 to 1.2%, mean age 58 years, 43% men). Erosive oesophagitis (OR = 2.99, 95% CI 1.58 to 5.66) and absence of dyspepsia (OR = 0.23, 95% CI 0.07 to 0.75) and Helicobacter pylori infection (OR = 0.41, 95% CI 0.19 to 0.92) were independent predictors for "eosinophils present". Definite eosinophilic oesophagitis was associated with dysphagia (2/66 vs 2/926, p = 0.025), and probable eosinophilic oesophagitis with narrowing of the oesophageal lumen (2/15 vs 5/978, p = 0.005). Conclusions: Oesophageal eosinophils were present in nearly 5% of the general population; approximately 1% had definite or probable eosinophilic oesophagitis. Oesophageal eosinophils may be a manifestation of reflux disease in adults, but the condition is as likely to be asymptomatic and go unrecognised.